Design, synthesis and biological evaluation of novel pyridine derivatives as gut-selective NaPi2b inhibitors. (1st June 2022) - Ushiki, Yasunobu; Kawabe, Kenichi; Yamamoto-Okada, Kumiko; Uneuchi, Fumito; Asanuma, Yuta; Yamaguchi, Chitose; Ohta, Hiroshi; Shibata, Tsuyoshi; Abe, Tomohiro; Okumura-Kitajima, Lisa; Kosai, Yuki; Endo, Mayumi; et al.
Graphical abstract: Abstract: We previously reported thiophene derivatives as gut-selective (minimally systemic) and potent sodium-dependent phosphate transport protein 2b (SLC34A2, NaPi2b) inhibitors. However, these derivatives did not suppress phosphate absorption form the intestinal tract in Sprague-Dawley (SD) rats. The lack of efficacy in vivo could be due to the high hydrophobicity of these compounds. In this report, we identified novel pyridine derivatives as gut-selective NaPi2b inhibitors with good activity in vitro and relatively low hydrophobicity. Especially, gut-selective compound 20b suppressed phosphate absorption in SD rats. These results suggest that physical properties, such as the hydrophobicity of the compounds, might affect the in vivo efficacy.